THE ROLE OF COMPENSATION IN IMPROVING EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS AN INTERVENING VARIABLE - Tabita, I Dewa Ayu Tita Permata (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
Human resources of a company are an important element. To promote strong employee performance, pay and encourage work motivation are necessary. On work motivation acting intervening variables, the aim of this study was to ascertain how salary affects employee performance. 37 individuals were included in the sample through saturation sampling or census. Both questionnaires and interviews were used to collect data. The Classical Assumption Test and the Path Analysis Test are the data analysis techniques used. The findings of this study show that salary has a direct impact on employee performance as well as an indirect impact through work motivation.